Analisis Hubungan Kemampuan Membaca Al-Qur’an dengan Pemahaman Ilmu Tajwid Mahasiswa PAI UIN Imam Bonjol Padang - Sya'adah, Miftahu; Kustati, Martin; Gusmirawati, Gusmirawati; Amelia, Rezki (Lembaga Yasin AlSys, 2024)
This study aims to examine the relationship between the ability to read the Qur'an and the understanding of Tajweed among Islamic Religious Education (PAI) students at UIN Imam Bonjol Padang. A good ability to read the Qur'an is expected to show a deep understanding of the science of tajweed, which includes the rules and regulations of reading in accordance with the provisions of the laws of tajweed. This study uses a quantitative approach with a correlational method to analyze the relationship between the two variables with a sample of 20 people from 150 populations by sampling with random sampling. The data were obtained by distributing questionnaires about the ability to read the Qur'an and understanding the science of Tajweed. The correlation analysis technique is used to see if there is a significant relationship between reading ability and understanding of Tajweed. The results showed that there is a significant positive correlation between the ability to read the Qur'an of PAI students of UIN Imam Bonjol Padang and the understanding of Tajweed. Based on the results of test analysis conducted on SPSS 20, the sig Asymp. Sig. (2-tailed) of 0.921> 0.05. Thus, in accordance with the basis of decision in the Kolmogorov-Smirnov normality test, it can be concluded that the data are normally distributed. Thus, the assumption or requirement of normality in the regression model is met.